Parent–Adolescent Socialization of Social Class in Low‐Income White Families: Theory, Research, and Future Directions. (18th August 2018) - Jones, Deborah J.; Loiselle, Raelyn; Highlander, April
Abstract : The formative role of social class in the United States has long been a focus of fields such as economics, history, and political science. Yet, little psychological theory or data are available to guide our understanding of what messages regarding social class are transmitted within and across generations and how those transmissions are most likely to occur. As a launching point for such work, we focus this initial contextual and largely theoretical review on parent–adolescent socialization of social class in low‐income, White families of adolescents in particular. To this end, our goal was to raise potential hypotheses about the implicit and explicit ways that White low‐income parents may shape adolescent views of class, as well as the meaning and implications of status socialization for adolescent health and well‐being.